(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses the concept of slang, the issues such as the importance of slang dictionaries and the increasing need for such dictionaries today are analyzed in tagging texts with slang. It focuses on the process of creating slang dictionaries, attaching slang annotations and other features to the text as tags in the corpus.